Congenital disorders sourcebook : basic consumer information about nonhereditary birth defects and disorders related to prematurity, gestational injuries, prenatal and perinatal infections, maternal health conditions during pregnancy, and birth complications, including cerebral palsy, cleft lip and palate, heart defects, hydrocephalus, spina bifida, and more ; along with facts about risk factors and birth defect prevention, prenatal care, fetal surgery techniques, and other treatment options, a glossary of related terms, and a directory of resources for additional help and information. (Health reference series., 2018)
"Provides consumer health information about nonhereditary birth defects and disorders, including facts about prevention and treatment options. Includes index, glossary of related terms, and other resources"--